2018
DOI: 10.1111/aor.13325
|View full text |Cite
|
Sign up to set email alerts
|

Zero‐Balance Ultrafiltration of Priming Blood Attenuates Procalcitonin and Improves the Respiratory Function in Infants After Cardiopulmonary Bypass: A Randomized Controlled Trial

Abstract: Blood priming is needed for cardiopulmonary bypass (CPB) in neonates and infants to avoid exceeding hemodilution; however, transfusion-related inflammation affects post-CPB outcomes in infant open-heart surgery. Procalcitonin, a newly detected inflammatory moderator and a sensitive parameter for predicting pulmonary dysfunction secondary to CPB, rises after CPB. We hypothesized that the hemofiltration of priming blood before CPB might decrease inflammatory mediators in the blood and post-CPB inflammatory repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
0
5
0
4
Order By: Relevance
“…The volumes of blood transfusion and bleeding were significantly lower in the Z‐BUF group than in the control group ( P = .001). The postoperative mechanical ventilation time was significantly low in the Z‐BUF group by comparison with the control group ( P = .03), and there was a statistically significant difference as regards the length of stay at the ICU between the 2 groups ( P = .02) …”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…The volumes of blood transfusion and bleeding were significantly lower in the Z‐BUF group than in the control group ( P = .001). The postoperative mechanical ventilation time was significantly low in the Z‐BUF group by comparison with the control group ( P = .03), and there was a statistically significant difference as regards the length of stay at the ICU between the 2 groups ( P = .02) …”
Section: Resultsmentioning
confidence: 94%
“…Our results revealed that the amounts of bleeding and blood transfusion were lower in the Z‐BUF group than in the control group. Gholampour et al reported that the ultrafiltration of stored blood before CPB was able to lessen the unfavorable effects of the stored blood and the production of inflammatory cytokines, which in turn significantly shortened the length of stay at the ICU and the duration of ventilation in their pediatric patients . It is worthy of note, however, that the method of ultrafiltration used by Shimpo and colleagues was hemofiltration rather than CUF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Maziar Gholampour Dehaki et al of the Rajaie Cardiovascular, Medical & Research Center—Perfusion, Tehran, Iran reported in a randomized controlled trial that zero‐balance ultrafiltration of priming blood attenuates procalcitonin and improves respiratory function in infants after CPB. Sixty infants were divided randomly into two equal groups of CPB with the zero‐balance ultrafiltration (Z‐BUF) of priming blood and CPB without it.…”
Section: Cardiopulmonary Support and Membrane Oxygenationmentioning
confidence: 99%